Análisis de vulnerabilidades en el tráfico de la red y estructura física del wifi en la Universidad Técnica de Babahoyo - Diaz Villacis, Denise Thalia (2021)
In this case study, an analysis of the network structure is carried out, how the Internet traffic flow of the WIFI service of the Technical University of Babahoyo is handled and analyzed, in order to detect possible failures and vulnerabilities that the network presents, A WIFI network analysis tool developed by the Ubiquiti company called WiFiman was used, which measured several main aspects which provided important data and information to study them and reach the relevant conclusions and provide recommendations to the possible failures that said red may have.